2017
DOI: 10.1186/s13690-017-0213-9
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle factors associated with underweight among Japanese adolescents: a cross-sectional study

Abstract: BackgroundBecause underweight in adolescents poses several health problems, it is important to prevent it in adolescence. For the prevention of underweight, it is necessary to investigate risk factors, especially lifestyles, because these can be modified. However, a limited number of studies exist regarding lifestyle factors associated with underweight among adolescents. The present study aimed to investigate the relationship between lifestyle factors and underweight among Japanese adolescents.MethodsStudy sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
5
11
1
Order By: Relevance
“…In a cross-sectional study of 2641 Japanese adolescents aged 12–13 years, adolescents who ate slowly were more likely to be underweight than were those who did not eat slowly. In keeping with the findings from the previous study [22], we also observed a negative association between the rate of eating and the prevalence of thinness. The children who ate slowly had a significantly higher prevalence of thinness in comparison with those in the reference group, while the children who ate fast had a significantly lower prevalence of thinness.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In a cross-sectional study of 2641 Japanese adolescents aged 12–13 years, adolescents who ate slowly were more likely to be underweight than were those who did not eat slowly. In keeping with the findings from the previous study [22], we also observed a negative association between the rate of eating and the prevalence of thinness. The children who ate slowly had a significantly higher prevalence of thinness in comparison with those in the reference group, while the children who ate fast had a significantly lower prevalence of thinness.…”
Section: Discussionsupporting
confidence: 92%
“…Although numerous epidemiological studies have examined the relationship between eating rate and obesity, to our knowledge, only one previous study has investigated the relationship between eating slowly and the prevalence of being underweight [22]. In a cross-sectional study of 2641 Japanese adolescents aged 12–13 years, adolescents who ate slowly were more likely to be underweight than were those who did not eat slowly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results on the effect of BMI on LE and HLE are backed by a study performed by Ochiai et al [37] which explained that underweight status was associated with scoliosis and osteoporosis – diseases that are not potentially life-threatening but can severely affect standards of living (affecting HLE and not LE). Governments should recognize that good nutrition is a priority for national health and prioritize nutritional quality in food assistance programs.…”
Section: Discussionsupporting
confidence: 71%
“…Underweight adolescents experience a higher risk of infectious diseases, more reduced cognitive function, psychiatric disorders, and poor perceived health. 3,4 For girls of childbearing age, underweight is particularly dangerous and associated with an array of adverse pregnancy outcomes, including maternal mortality, preterm birth, and intrauterine growth retardation. 3 Obese children are at increased risk of becoming obese adults 5 and consequently at higher risk for cardiovascular disease, diabetes, and other costly chronic comorbidities.…”
Section: Introductionmentioning
confidence: 99%